D’arisun AR: Integrating Sundanese Ethnomathematics and Augmented Reality to Enhance Elementary Students’ Understanding of Number Patterns - Mahmud Masulin; Annasya Syiffa Syahida; Nabilah Mumtaz; Eleonora Nabillah Putri; Susi Rohani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Mathematics learning in elementary schools often faces challenges related to low conceptual understanding, limited critical thinking skills, and the lack of innovative digital media integrated with local culture. This preliminary study aims to analyze the need for developing D’arisun AR (Deret Aritmatika dan Sunda), an Augmented Reality-based learning media grounded in Sundanese ethnomathematics to support third-grade students’ understanding of arithmetic sequences. A descriptive mixed-method design was employed. Data were collected from three public elementary schools in Tapos District, Depok City, through documentation of mathematics assessment scores (N = 90 students) and semi-structured interviews with three teachers and nine students. The findings showed that the average mathematics scores were 70, 66, and 68, all below the Minimum Mastery Criterion (75). Interviews revealed that students experienced difficulties in identifying numerical patterns and solving contextual mathematical problems. Teachers rarely used interactive technology-based media, and local cultural elements had not been integrated into mathematics instruction. Meanwhile, students showed strong interest in mobile learning applications and culturally contextual learning activities. The findings indicate the need for an ethnomathematics-based Augmented Reality learning media that can visualize arithmetic sequence patterns through Sundanese cultural representations, such as Mega Mendung batik motifs and traditional games. Therefore, this study recommends the development of D’arisun AR using the 4-D development model to support meaningful, contextual, and culturally responsive mathematics learning.